Effect of polymer topology on non-covalently bonded polyesters - Süsler, Göknil. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Synthetic polymers have a crucial role in our daily lives. The irreversible nature of covalent bonding in conventional synthetic polymers makes them non-recyclable and prevents re-processing of the materials. Throughout the years with the development in technology, the demand for more advanced materials such as, reversible, recycable, and reprocessable materials has increased. Supramolecular chemistry has emerged to solve this need for reversibility in polymer materials. Supramolecular polymers are more tunable and dynamic due to their non-covalent and reversible nature. Non-covalent interactions include metal-ligand coordinations, host-guest, π – π stacking, ionic interactions and hydrogen bonding. Ionic hydrogen bonding has the known characteristics of hydrogen bonding such as directionality, strength and versatility. For instance, a carboxylic acid and an amine give rise to ionic hydrogen bonding by acid-base complexation reaction. Thus, carboxyl-terminated polyesters, in principle, may coordinate with amines to produce supramolecular materials. In this study, the carboxyl-terminated polyesters and amines having different functionalities were mixed/reacted in a melt reactor to form acid-base coordinates. The thermal and mechanical properties of the amine treated polyesters were investigated through DSC and rheometric measurements, respectively.
Keywords: Polymers -- Analysis.; Synthetic products -- Analysis.